Madison State of Mind: Demographics and Urban Form on State Street - Roberts, Dave; Puerling, Dan; Ludtke, Morgan; Baker, Will (My University, 2013)
The 500 block of State Street, in downtown Madison, Wisconsin, is currently undergoing a radical landscape change through the construction of a new high rise apartment complex called ?The Hub?. This study seeks to discover why changes in the built environment of State Street occur and specifically investigates the relationship between the demographics in the immediate vicinity and the built environment of State Street. Demographic data provided by the census website Social Explorer, built environment data provided by the city directories of Madison, and survey data provided by a range of survey respondents reveal that contrary to what is typically found in literature, the built environment of State Street does not appear to be driven by demographics, or vice versa. Rather there are signs that time, and not demographics, seem to be the driving force for the built environment on State Street. As time passes, popular culture changes with it. In turn State Street business adapt to popular demand.
Includes Appendices, Illustrations, Photographs, Charts and Bibliography.
Keywords: Built environment; Urban form; Demographics; Madison